Research on the relationship between controlling shareholders’ equity pledging behavior and corporate financial risk of listed companies in China - Sun, Xi-ze (2022)
This study examines the impact of equity pledges on financial risk. The growing popularity of equity pledges due to their high degree of flexibility can also have certain negative effects on companies. In China, since the lowering of the threshold for equity pledges in 2013, equity pledge financing has grown exponentially and financial problems arising have gradually emerged. The objective of this study is to investigate the effect of controlling shareholders’ equity pledging behavior on corporate financial risk and to investigate the moderating effect of equity concentration on both. This research mainly investigates the proportion of equity pledges and the flow of pledged funds. This study uses a quantitative approach to collect data for Chinese listed companies from 2013 to 2020 and conducts empirical analyses using Stata 16.0.